Investigation of plasma asprosin and saliva levels in newly diagnosed type 2 diabetes mellitus patients treated with metformin - Gozel, Nevzat; Kilinc, Faruk (Via Medica, 2021)
Introduction: Asprosin is a hormone that was first reported by Romere et al. [2016]. Its secretion is induced in the case of starvation. Asprosin promotes hepatic glucose release. There is no literature information available in humans to demonstrate how blood and saliva asprosin levels of patients with the newly identified type 2 diabetes mellitus (T2DM) changed after metformin treatment. We aim to examine these changes and contribute to the literature in this sense. Material and methods: A total of 60 individuals: 30 healthy volunteers and 30 newly identified cases of T2DM whose treatment had been initiated, were included in the investigation. Blood and saliva sample specimens were carefully taken from both groups. Saliva asprosin and serum levels were tested using the ELISA method. Immunohistochemical methods were used to test asprosin formation sites in salivary gland tissues. Results: Similarly increased asprosin levels were observed in patients from the newly diagnosed T2DM group compared with the healthy control group (p = 0.003). In the newly defined T2DM group, blood asprosin levels decreased significantly after three months of metformin treatment (p = 0.032). In terms of saliva asprosin levels, when the healthy control group and the newly identified T2DM group were compared, saliva asprosin levels were found to be higher in the newly identified T2DM group (p < 0.001). With immunohistochemical staining, asprosin immunoreactivity was observed in the submandibular and parotid glands. Conclusions: In our study, serum and saliva asprosin levels increased significantly in the newly identified individuals with type 2 diabetes, which suggests that asprosin could form a critical risk related to T2DM. Higher asprosin levels are an important marker for predicting diabetes development, and that this hormone can be signified as a main or target molecule in the treatment of diabetes.
Keywords: type 2 diabetes mellitus; asprosin; metformin